Jesuits Working in Spanish State‑Run Universities, 1950-1990 - Udías Vallina, Agustín (Razón y fe, 2026)
From 1950 a presence of young Jesuits studying in state public universities and afterwards as professors at different levels began in Spain. Similarly, it happened also with researchers at the CSIC. This incorporation was possible due to the large number of vocations to the Society of Jesus in Spain in those years and the rapid increase in the university students and professors between 1955 and 1975. From 1973, this Jesuit involvement was formalized in 1976 with the creation of the University Mission in Non-Jesuit Institutions (MUINSI). In the years of greater participation about 1986 there were some 75 Jesuits working in public universities and the CSIC, among them 23 full professors, 9 in humanities and 14 in science. The rapid fall in vocations from 1980 on and the needs of the own institutions and other forms of work determined the end of this experience.
Keywords: Jesuits; university professors; state universities; CSIC; MUINSI; evolution